Pengaruh Perilaku Pimpinan dan Praktik Manajemen Sumber Daya Manusia terhadap Budaya Organisasi dan Kinerja Bank Perkreditan Rakyat di Jawa Timur - Melinda, Tina (Jurnal Widya Manajemen & Akuntansi, 2006)
The aims of the research are: 1) to analyze and prove the influence of leader's behavior factor to organization culture 2) to analyze and prove the influence of leader's behavior factor to organization performance 3) to analyze and prove the influence of human resources management factor to organization culture 4)to analyze and prove the influence of human resources management factor to organization performance. On the other hand, organization culture has negative influence to performance especially bureaucracy in organization culture which has significant contribution in reducing BPR performance. Thus, it is suggested that management shouldn't create bureaucratic atmosphere within the organization.